82.5k views
1 vote
(6x + 2) - (3x + 3) = 82

User Shrm
by
7.6k points

1 Answer

5 votes

Answer:


\sf x =(83)/(3) \textsf{ Or } 27.666666666666

Explanation:

To solve the equation (6x + 2) - (3x + 3) = 82, we can follow these steps:

Distribute the negative sign in front of the second set of parentheses:

6x + 2 - (3x + 3) = 82

6x + 2 - 3x - 3 = 82

Combine like terms on the left-hand side of the equation:

3x - 1 = 82

Add 1 to both sides of the equation:

3x - 1 + 1 = 82 + 1

3x = 83

Divide both sides of the equation by 3 to get the solution:


\sf (3x)/(3)=(83)/(3)


\sf x =(83)/(3) \textsf{ Or } 27.666666666666

Therefore, the solution to the equation (6x + 2) - (3x + 3) = 82 is:


\sf x =(83)/(3) \textsf{ Or } 27.666666666666

User SandOfTime
by
8.9k points